I spy a skeleton - Marzollo, Jean.; Wick, Walter (New York : Scholastic, 2009)
Contains riddles that challenge readers to find various objects hidden in spooky photographs.
"Cartwheel books."
3.9
K-3.
K-3
Keywords: Picture puzzles -- Juvenile literature; Skeleton -- Juvenile literature; Picture puzzles; Skeleton; Picture puzzles; Skeleton; Readers (Elementary).